Pengaruh Entertainment dan Informativeness terhadap Keputusan Berpartisipasi dalam Mengikuti Event Talks - Vanda Nirma Audita; Moch Liga Suryadana; Sukmadi (Politeknik Pariwisata NHI Bandung, 2023)
Indonesia Event Industry Council (IVENDO) in 2020 showed that 43% of events were canceled and 48% were postponed during the pandemic. One of the innovations that are considered to be able to provide solutions for the current event industry is virtual events. One that adapts the implementation of virtual events is the convention and event management study program from the Bandung NHI Tourism Polytechnic which applies practical activities by implementing virtual events. The event held is a webinar series with the name event talks. This study aims to examine the effect of the entertainment variable and informativeness variable on the decision to participate in event talks. This research was conducted with a quantitative approach by distributing questionnaires to 165 respondents from year 2022 who had participated in event talks using a purposive sampling technique. The theory used is the entertainment theory of Horner (2005), the theory of informativeness from Suyanto (2000), and the theory of participating decisions from Allen (2011). The results of the study explain that entertainment and informatics significantly influence the decision to participate in event talks by 37.6% while the remaining 62.4% is influenced by other variables not examined in this study. Thus, in the future, the organizers can pay attention to aspects of other variables that can be an attraction for potential participants.